Application of SPSS in the Analysis of Comprehensive Results of Specially Selected Public Physical Education Classes -- Take the example of "Taekwondo" Special Selection Class - Yajun Qiao (Forest Chemicals Review, 1970)
In today's highly informative society, educators need to master advanced data analysis methods to analyze data information with breadth, depth, and high accuracy, and to obtain more accurate conclusions to provide a data reference for the development of the field. The SPSS software is a tool for statistical products and services, and its high level of automation and accuracy can greatly reduce the burden of statistical analysis on teachers. In this paper, the author analyzes 346 comprehensive results (before the make-up exams) of the 2021 class of Taekwondo at an institution of higher learning to verify the effectiveness of classroom instruction and to propose reference solutions for the development of the discipline.